2012
DOI: 10.1007/s13337-012-0090-3
|View full text |Cite
|
Sign up to set email alerts
|

Production and Application of Polyclonal Antibodies Against Recombinant Capsid Protein of Extra Small Virus of Macrobrachium rosenbergii

Abstract: Macrobrachium rosenbergii nodavirus along with a satellite virus, extra small virus (XSV) causes white tail disease (WTD) in the giant freshwater prawn M. rosenbergii. Infected M. rosenbergii postlarvae were collected from a hatchery in Kakinada, Andhra Pradesh. The gene coding the capsid protein of XSV was cloned in a bacterial expression vector pRSET A and the recombinant protein was expressed in Escherichia coli BL21(DE3)pLysS cells. The recombinant protein was purified by Nickel affinity chromatography. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Available antibody-based diagnostic methods for MrNV includes S-ELISA [30] and TAS-ELISA [26] and for XSV, it is polyclonal antibodies raised against the whole virus [33] and recombinant viral protein [21]. In the majority of cases, antibodies were produced against the whole virus.…”
Section: Specificity and Sensitivity Of Polyclonal Antibodies In Detection Of Mrnv And Xsv Antigensmentioning
confidence: 99%
“…Available antibody-based diagnostic methods for MrNV includes S-ELISA [30] and TAS-ELISA [26] and for XSV, it is polyclonal antibodies raised against the whole virus [33] and recombinant viral protein [21]. In the majority of cases, antibodies were produced against the whole virus.…”
Section: Specificity and Sensitivity Of Polyclonal Antibodies In Detection Of Mrnv And Xsv Antigensmentioning
confidence: 99%
“…The genome of Mr NV consists of two single‐stranded positive‐sense RNA molecules encoding RNA‐dependent RNA polymerase (RdRp), B2 protein and a capsid protein (Bonami et al., 2005; Hayakijkosol et al., 2012; Low et al., 2018; NaveenKumar, 2017; NaveenKumar, Karunasagar et al., 2013; NaveenKumar, Shekar, et al., 2013). The smaller virus among the two XSV is also non‐enveloped, 14–16 nm diameter with a single‐stranded positive‐sense RNA genome of approximately 0.8 kilobases (Qian et al., 2003; Sri Widada & Bonami, 2004) which codes for two overlapping structural (capsid) proteins of size 16 and 17 kDa (Neethi et al., 2012; Wang et al., 2008). Due to its small size and absence of RdRp or enzymes required for replication, it has been suggested that XSV may be a satellite virus and replication depends on its helper virus, Mr NV in this case (Sri Widada & Bonami, 2004; Zhang et al., 2006).…”
Section: Introductionmentioning
confidence: 99%